Exploring bacterial interspecific interactions for discovery of novel antimicrobial compounds. Issue 4 (29th May 2017) - Tyc, Olaf; de Jager, Victor C.L.; van den Berg, Marlies; Gerards, Saskia; Janssens, Thierry K.S.; Zaagman, Niels; Kai, Marco; Svatos, Ales; Zweers, Hans; Hordijk, Cornelis; Besselink, Harrie; de Boer, Wietse; et al.
Summary: Recent studies indicated that the production of secondary metabolites by soil bacteria can be triggered by interspecific interactions. However, little is known to date about interspecific interactions between Gram‐positive and Gram‐negative bacteria. In this study, we aimed to understand how the interspecific interaction between the Gram‐positive Paenibacillus sp. AD87 and the Gram‐negative Burkholderia sp. AD24 affects the fitness, gene expression and the production of soluble and volatile secondary metabolites of both bacteria. To obtain better insight into this interaction, transcriptome and metabolome analyses were performed. Our results revealed that the interaction between the two bacteria affected their fitness, gene expression and the production of secondary metabolites. During interaction, the growth of Paenibacillus was not affected, whereas the growth of Burkholderia was inhibited at 48 and 72 h. Transcriptome analysis revealed that the interaction between Burkholderia and Paenibacillus caused significant transcriptional changes in both bacteria as compared to the monocultures. The metabolomic analysis revealed that the interaction increased the production of specific volatile and soluble antimicrobial compounds such as 2, 5‐bis(1‐methylethyl)‐pyrazine and an unknown Pederin‐like compound. The pyrazine volatile compound produced by Paenibacillus was subjected to bioassays and showed strong inhibitory activity against Burkholderia and a range of plant and human pathogens. Moreover, strong additive antimicrobial effects were observed when soluble extracts from the interacting bacteria were combined with the pure 2, 5‐bis(1‐methylethyl)‐pyrazine. The results obtained in this study highlight the importance to explore bacterial interspecific interactions to discover novel secondary metabolites and to perform simultaneously metabolomics of both, soluble and volatile compounds. Abstract : The production of secondary metabolites by soil bacteria can be affected by interspecific interactions. In this study, we aimed to understand how the interspecific interaction between the Gram‐positive Paenibacillus sp. AD87 and the Gram‐negative Burkholderia sp. AD24 affects fitness, gene expression and the production of soluble and volatile secondary metabolites. Our results revealed that the interaction between the two bacteria affected their fitness, gene expression and the production of secondary metabolites.